The physician’s role in perioperative management of older patients undergoing surgery - Gordon, Adam L.; Evans, Barry J.; Dhesi, Jugdeep (Royal College of Physicians, 2017)
Life-sustaining and life-improving surgical interventions are increasingly available to older, frailer patients, many of whom have multimorbidity. Physicians can help support perioperative multidisciplinary teams with assessment and preoperative optimisation of physiological reserve, comorbidities and associated geriatric syndromes. Similar structured support can be useful in the postoperative period where older patients are at increased risk of delirium, medical complications, increased functional dependency and where discharge planning can prove more difficult than in younger cohorts. Comprehensive geriatric assessment has been shown to improve outcomes and is now embedded in most UK-based services for traumatic hip fracture. Perioperative comprehensive geriatric assessment has been explored in other surgical disciplines and procedures and, where evaluated, has been associated with improved outcomes. The need to support older patients with frailty undergoing surgery exceeds the capacity of specialist geriatricians. Other groups of healthcare professionals need to nurture the core competencies to support this group perioperatively.